Digital Islamic Da'wah Literacy Framework untuk Ekonomi Syariah Berkelanjutan - Intihaul Khiyaroh (Al-Musthofa: Journal of Sharia Economics, 2026)
This research aims to analyze the role of digital da'wah communication in enhancing sharia economic literacy among Muslim communities through the integration of Islamic values and digital media strategies. (2) Using a qualitative method with a digital communication ethnography approach, the study was conducted through observation of da'wah content on ten YouTube and Instagram accounts, as well as in-depth interviews with digital preachers, Islamic finance practitioners, and millennial Muslim audiences. (3) The findings reveal that digital da'wah communication not only conveys sharia economic information but also instills spiritual and moral values in economic behavior. Three main dimensions were identified: religious-normative (trust and justice values), educative-informative (understanding of sharia finance), and symbolic-interactive (use of visual media and religious narratives). This research produces a conceptual model, the Digital Islamic Da'wah Literacy Framework, which illustrates the contribution of digital da'wah in strengthening a sustainable and just Islamic economic ecosystem.